Am I prepared for Calculus? An action-research study of female students emerging from patriarchy - Waheed, Saira; Pilotti, Maura A. E.; AbdelSalam, Hanadi M. (Frontiers in Education, 2024)
The present study takes a snapshot of the views that Saudi Arabian female undergraduate students hold of their Math prerequisite competency. They are enrolled in Calculus, a course that is at the core of their ability to successfully pursue a STEM degree in Engineering and Computer Science. As Saudi Arabian undergraduate students, they are under intense pressure to succeed academically and professionally in a changing socio-economic context. As females, they are seen by their government as the key contributors to a society that is rapidly restructuring itself to support a knowledge and service-based economy. Yet, they are at every step confronted with the remnants of a patriarchal system of gender stereotypes, which may discount their accomplishments. In the present study, we specifically examine (a) how this rather distinctive sample of students may self-evaluate their Math prerequisite competency and (b) how they perform on a test assessing such competency. Of interest is to determine students’ degree of awareness of their Math knowledge and skills at the start of Calculus.